2017
DOI: 10.1021/acs.bioconjchem.7b00141
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Fluorides: Fast, Efficient, and Versatile Lysine-Based Protein Conjugation via Plug-and-Play Strategy

Abstract: We report a plug-and-play strategy for the preparation of functionally enhanced antibodies with a defined average degree of conjugation (DoC). The first stage (plug) allows the controllable and efficient installation of azide groups on lysine residues of a native antibody using 4-azidobenzoyl fluoride. The second step (play) allows for versatile antibody functionalization with a single payload or combination of payloads, such as a toxin, a fluorophore, or an oligonucleotide, via copper-free strain-promoted azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…The O ‐terminus of 5 is then converted to an amino group giving intermediate 6 , a protected CA (PEG) n . Alternatively, addition of amino‐polyethylene glycol 3 to acrylate 4 gives directly the intermediate 6 [7a–e]. Deprotection and hydrolysis of the intermediate 6 complete the synthesis of CA (PEG) n ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The O ‐terminus of 5 is then converted to an amino group giving intermediate 6 , a protected CA (PEG) n . Alternatively, addition of amino‐polyethylene glycol 3 to acrylate 4 gives directly the intermediate 6 [7a–e]. Deprotection and hydrolysis of the intermediate 6 complete the synthesis of CA (PEG) n ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To be efficient and practical, synthesis plan A demands that the acrylate [1‐ 14 C]‐ 4 be the limiting reagent in the oxa‐Michael addition and the yield of the adduct be good. It came to our attention that the reported oxa‐Michael addition of amino‐polyethylene glycol 3 to acrylate 4 has been achieved using an excess (greater than or equal to 1.5 Eq) of acrylate [7a–e]. Furthermore, the yield of the adduct in the limited number of reported cases was generally moderate,[7a–d] yet low yields and failed reactions have also been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acyl fluorides are carboxylic acid derivatives that contain af luorocarbonyl group.B ecause of the electrostatic stability of the CÀFb ond, [1] acyl fluorides are more stable than comparable acyl halides,s uch as acyl chlorides,t owards solvolysis,i ncluding hydrolysis, [2] alcoholysis, [3] and aminolysis. [4] Accordingly,t hey are regarded as easy-to-handle and versatile potential alternatives to carboxylic acids.A cyl fluorides have traditionally been used as acylationr eagents for nucleophilic molecules,w hereby the acyl CÀFb onds are converted into the corresponding acyl CÀXbonds.Especially in peptide chemistry,t he derivatization of amino acids into the corresponding acyl fluorides is aw ell-documented strategy for peptide coupling [5,6] through the formation of acyl C À Nb onds, [7,8] as the use of a-amino acid fluorides generates the corresponding amides in good yields without racemization. Aside from peptide coupling reactions,numerous reactions have been reported that involve various nucleophiles and the formation of acyl CÀXb onds,f or example,the formation of acyl C À C [9][10][11] and C À O [12,13] bonds, and other related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonsäurefluoride fanden traditionell Verwendung als Acylierungsmittel fürn ucleophile Moleküle,w obei die C-F-Bindungen der Carbonsäurederivate in die jeweiligen C-X-Bindungen umgewandelt werden. Besonders in der Peptidchemie ist die Derivatisierung von Aminosäuren zu den entsprechenden Säurefluoriden eine gut dokumentierte Strategie der Peptidkupplung [5,6] über die Bildung von C(Acyl)-N-Bindungen, [7,8] da der Einsatz von a-Aminosäurefluoriden die jeweiligen Amide in guten Ausbeuten ohne Racemisierung liefert. Außer Peptidkupplungen wurden auch zahlreiche Reaktionen unter Beteiligung diverser Nucleophile und der Bildung von C(Acyl)-X-Bindungen, beispielsweise von C-(Acyl)-C- [9][10][11] und C(Acyl)-O-Bindungen, [12,13] sowie verwandte Reaktionen [14][15][16] beschrieben.…”
Section: Introductionunclassified